The Effect of Suspension Training and Dumbbell Training on Increasing Muscle Endurance in the Elderly - ARTASONIA, LUCKYTA (Jurnal Ilmiah Fisioterapi Muhammadiyah, 2024)
Abstract To determine the difference in the provision of suspension training and dumbbell training on increasing muscle endurance in the elderly. This study is experimental which was conducted 2 times a week for 4 weeks at Perkumpulan Senam Lansia Kelurahan Cibubur. This study consisted of 20 people and was divided into two groups of 10 people each, namely treatment group I given Suspension Training and treatment group II given Dumbbell Training. Each group of muscle endurance improvement was measured with the Arm (Biceps) Curl Test and 30 Second Chair Stand Test. This research is experimental which was conducted 2 times a week for 4 weeks at Perkumpulan Senam Lansia Kelurahan Cibubur. This study consisted of 20 people and was divided into two groups of 10 people each, namely treatment group I given Suspension Training and treatment group II given Dumbbell Training. Each group increased muscle endurance measured by the Arm (Biceps) Curl Test and 30 Second Chair Stand Test. Results: In this study successfully showed that Suspension Training pre test ACBT mean ± SD is 18.60 ± 4.138, the results of the post test ACBT mean ± SD is 19.90 ± 4.202. Pre test 30s CST mean ± SD is 11.60 ± 1.838, the results of the post test 30s CST mean ± SD is 13.20 ± 2.486. In the Dumbbell Training study, the results of the ACBT pre test mean ± SD were 18.50 ± 4.275, the results of the ACBT post test mean ± SD were 19.50 ± 4.552. Pre test 30s CST mean ± SD is 11.40 ± 2.547, the results of the post test 30s CST mean ± SD is 12.40 ± 2.271. Both of these studies showed a significant increase in muscle endurance in the elderly between before and after treatment (p < 0.05). However, the difference test between Suspension Training and Dumbbell Training on increasing muscle endurance did not show a significant difference (p = 0.273). Suspension Training and Dumbbell Training can significantly increase muscle endurance in the elderly but the two methods do not show a significant difference in the results. Keywords: suspension training, dumbbell training, arm (biceps) curl test, 30 second chair stand test, elderly